Self-dual Chern-Simons solitons in non-commutative space - Lozano, Gustavo Sergio (2001)
We construct exact soliton solutions to the Chern-Simons-Higgs system in non-commutative space, for non-relativistic and relativistic models. In both cases we find regular vortex-like solutions to the BPS equations which approach the ordinary selfdual non-topological and topological solitons when he non-commutative parameter θ goes to zero.